2012
DOI: 10.1017/s1049023x12001392
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Prescription of Antidepressant and Anxiolytic Drugs after Cyclone Yasi in North Queensland

Abstract: There was a quantifiable increase in the prescription of antidepressant drugs following Cyclone Yasi that may indicate an increase in psychosocial distress in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 23 publications
2
22
0
9
Order By: Relevance
“…A disaster is an unanticipated, large-scale, catastrophic event that threatens the lives of individuals or a large group of people, and can cause social network collapse, the substantial loss of social resources, and adverse effects on community physical and mental health status (Birur et al, 2017). Traumatic events related to disaster can lead to severe, long-lasting psychological distress at an individual or population level (Usher et al, 2012). Previous studies have documented the increased prevalence of psychiatric conditions such as depression, anxiety, suicidal behaviors, post-traumatic symptoms, and substance abuse in the aftermath of disasters (Birur et al, 2017;Kolves et al, 2013;Tang et al, 2014;Vlahov et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A disaster is an unanticipated, large-scale, catastrophic event that threatens the lives of individuals or a large group of people, and can cause social network collapse, the substantial loss of social resources, and adverse effects on community physical and mental health status (Birur et al, 2017). Traumatic events related to disaster can lead to severe, long-lasting psychological distress at an individual or population level (Usher et al, 2012). Previous studies have documented the increased prevalence of psychiatric conditions such as depression, anxiety, suicidal behaviors, post-traumatic symptoms, and substance abuse in the aftermath of disasters (Birur et al, 2017;Kolves et al, 2013;Tang et al, 2014;Vlahov et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…12,13 However, it differs from an Australian study that showed a decrease in prescriptions of anti-anxiety medications immediately after a cyclone but an increase over a six-month period. 16 A possible explanation is that this Australian study looked at overall rates of prescriptions, whereas the current study looked at new prescriptions among individuals who had not had a previous prescription in the preceding year, and this specificity allowed for the detection of a signal. As ED data were not available for High River, we were unable to look for other indicators of psychological health.…”
Section: Mental Health and Violencementioning
confidence: 94%
“…11 Monitoring prescription drug changes can provide an indirect measure of psychological distress in the population. [14][15][16] Psychological stress has been associated with externalized behaviour such as substance abuse and violence. 17 An increase in violence following a disaster has been observed in some studies.…”
mentioning
confidence: 99%
“…Evaluation of psychiatric medication dispensing following a disaster is an established tool to provide an indirect measure of community psychiatric morbidity . The use of dispensing data can address key methodological weaknesses highlighted in reviews of the disaster literature.…”
Section: Introductionmentioning
confidence: 99%